2020
DOI: 10.3390/ijerph17072488
|View full text |Cite
|
Sign up to set email alerts
|

Association between Reallocation Behaviors and Subjective Health and Stress in South Korean Adults: An Isotemporal Substitution Model

Abstract: This study used an isotemporal substitution (IS) model to determine the potential reallocation effects of sedentary behavior (SB) and physical activity (PA) on subjective health and stress in South Koreans with data from the Sixth Korean National Health and Nutrition Examination Survey 2015. The analysis included 791 participants whose accelerometer-measured PA was available, divided into three age groups (young adults = 151; mid-age adults = 334; older adults = 306). We adopted SB, light PA (LPA), and moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
0
12
3
Order By: Relevance
“…These comparisons should, however, be taken with caution, because the latent classes in the Oftedal et al [44,45] studies were based not only on movement behaviours but also on dietary habits. Furthermore, two other previous studies [46,47] did not find a significant association between movement behaviours and stress, possibly because of their significantly smaller sample sizes compared to the current study. In our study, the strength of the association with stress frequency was almost identical across the groups meeting a combination of any two guidelines.…”
Section: Comparison With Previous Studiescontrasting
confidence: 81%
“…These comparisons should, however, be taken with caution, because the latent classes in the Oftedal et al [44,45] studies were based not only on movement behaviours but also on dietary habits. Furthermore, two other previous studies [46,47] did not find a significant association between movement behaviours and stress, possibly because of their significantly smaller sample sizes compared to the current study. In our study, the strength of the association with stress frequency was almost identical across the groups meeting a combination of any two guidelines.…”
Section: Comparison With Previous Studiescontrasting
confidence: 81%
“…These comparisons should, however, be taken with caution, because the latent classes in the Oftedal et al (44,45) studies were based not only on movement behaviours but also on dietary habits. Furthermore, two other previous studies (46,47) did not nd a signi cant association between movement behaviours and stress, possibly because of their signi cantly smaller sample sizes compared to the current study. In our study, the strength of the association with stress frequency was almost identical across the groups meeting a combination of any two guidelines.…”
Section: Comparison With Previous Studiescontrasting
confidence: 80%
“…The positive association of MVPA with self-rated health among adults (while considering other movement behaviours) was also found in the von Rosen and Hagströmer (48) study. Similarly, results of the Park et al(47) study suggested that increasing the time spent in MVPA at the expense of the time spent in SB is associated with better self-rated health in adults. Within the composition of movement behaviours, MVPA often shows the strongest positive association with health…”
mentioning
confidence: 78%
See 2 more Smart Citations